Beach pug - May, Kyla (May, Kyla. Diary of a pug, 2024)
It is Bub the pug's first trip to the beach, and Bella wants to enter him in a pet-surfing contest, but Bub is scared of the ocean and refuses, so he hopes to make it up to Bella by presenting her with the treasure at the end of the map he found.